2020
DOI: 10.1002/mar.21335
|View full text |Cite
|
Sign up to set email alerts
|

Spillover effects from unintended trials on attitude and behavior: Promoting new products through access‐based services

Abstract: Access-based services (ABS) provide an opportunity for brands to promote their new products by enabling (unintended) trials. However, the mechanisms and impact of consumer exposure to products in ABS and the subsequent potential spillover effects on both the brand and the product perception are largely unknown.Our hypotheses are derived from the information integration theory (IIT) and subsequently tested. Study 1 is a field study investigating an unintended trial moderated by involvement and positive experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 104 publications
(135 reference statements)
0
13
0
Order By: Relevance
“…Concerning the financial perception (H3 and H4) and capacity factors (H5 and H6) of the bike, Lehr et al (2020) confirmed that user involvement could increase intentions, but how? Therefore, parallel to their suggestion of using information integration theory, our study also supports that Chinese policies should try to offer the maximum unintended trial by explaining our research insights.…”
Section: Resultsmentioning
confidence: 76%
“…Concerning the financial perception (H3 and H4) and capacity factors (H5 and H6) of the bike, Lehr et al (2020) confirmed that user involvement could increase intentions, but how? Therefore, parallel to their suggestion of using information integration theory, our study also supports that Chinese policies should try to offer the maximum unintended trial by explaining our research insights.…”
Section: Resultsmentioning
confidence: 76%
“…The sharing economy has gained increasing attention as an alternative to ownership‐centric modes of consumption. Defined as “a scalable socioeconomic system that employs technology‐enabled platforms to provide users with temporary access to tangible and intangible resources” (Eckhardt et al, 2019, p. 7), it comprises a variety of business models, such as peer‐to‐peer sharing platforms (e.g., Benoit et al, 2017; Stofberg & Bridoux, 2019), access‐based services from professional service providers, such as car sharing or fashion rentals (e.g., Lehr et al, 2020), or business‐to‐business services that replace ownership of industrial machinery (e.g., Schaefers et al, 2021). Although the COVID‐19 pandemic has severely affected some sharing economy business models, such as accommodation and transportation, the ongoing digital transformation appears to continue to drive the adoption of access‐as‐a‐service in a post‐pandemic world (Batool et al, 2020; Hossain, 2021; Meenakshi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…S = stimuli, Ψ = goal-oriented values of the stimuli, ρ = unitary response, R = observable response (Anderson, 2016;Klitzner & Anderson, 1977). In contrast, most studies of product evaluations and attitude changes have applied the adding or averaging law (Anderson, 1965;Lehr, Buettgen, Benoit, & Merfeld, 2020;Schumann, Wünderlich, & Evanschitzky, 2014;Simonin & Ruth, 1998). Anderson (2013Anderson ( , 2016 also noted that the application of the averaging law has been by far the most frequent overall.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Researchers have mostly applied the multiplying law to studies of behaviour under uncertainty, such as gambling or gaming, where expected outcome is multiplied by expected probability to determine behavioural tendency (Anderson, 2016; Klitzner & Anderson, 1977). In contrast, most studies of product evaluations and attitude changes have applied the adding or averaging law (Anderson, 1965; Lehr, Buettgen, Benoit, & Merfeld, 2020; Schumann, Wünderlich, & Evanschitzky, 2014; Simonin & Ruth, 1998). Anderson (2013, 2016) also noted that the application of the averaging law has been by far the most frequent overall.…”
Section: Theory and Hypothesesmentioning
confidence: 99%